Molecular detection of virulence genes for Candidiasis associated with corona virus disease in patients of Wasit Governorate (Eurasian Medical Research Periodical, 2022)
Respiratory infections caused by fungal pathogens present a growing global health concern and are a major cause of death in immunocompromised patients. Worryingly, corona virus disease-19 (COVID-19) resulting in acute respiratory distress syndrome has been shown to predispose some patients to airborne fungal co-infections. The aims of Study are: Isolation and identification of fungal pathogens from patients with corona virus infections and Molecular documentation of the most common fungal isolate and detection some virulence genes